Studies in law, politics, and society - Sarat, Austin (Bingley, U.K. : Emerald, 2016)
Studies in Law, Politics, and Society (SLPS) provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship; the articles in this volume cover a diverse range of topics relating to law's relationship with and impact on society. Topics covered include: coverage of capital punishment in the mainstream and radical press; the landmark Roe vs. Wade case and the Republican Party's relationship with abortion law; an exploration of the legal politics of temporality in emergencies; gendered racialization and White supremacy in the US, specifically related to Muslim women; conflict resolution and legal theory; and self-determination for indigenous peoples in the Pacific.
A twice told story: comparing accounts of capital punishment in the radical and mainstream press / Austin Sarat, Kyra Ellis-Moore, Abraham Kanter, Christina Won, Abigail Xu -- Why Roe still stands: abortion law, the Supreme Court, and the Republican regime / Thomas Keck, Kevin McMahon -- The legal politics of time in emergencies: ticking-time in the Israeli High Court of Justice / Karin Loevy -- Between society and the state: gendered racialization and Muslim Americans / Hajer Al-Faham, Rose Ernst -- The <U+201c>Law of Alternatives<U+201d>: conflict resolution as the art of reconstruction / Michal Alberstein -- Decolonization and the right of self-determination for the Pacific / Valmaine Toki.
Includes bibliographical references.
Print version record
Keywords: Political Science -- Public Policy -- Social Policy; Law & society; Sociological jurisprudence